DESIGN FOR A BI-PLANETARY GEAR TRAIN - Józef DREWNIAK; Paulina GARLICKA; Aleksandra KOLBER (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents the design for a bi-planetary gear train. The project description is supplemented with calculations of kinematics, statics and meshing efficiency of the gear wheels included in the gear train. Excluded are calculations of strength and geometry of gears, shaft and rolling bearing, since they are similar to classical calculations for planetary gears. An assembly drawing in 2D and assembly drawings in 3D of the designed bi-planetary gear train are also shown. This gear train will form the main element of the research in hand.